2022
DOI: 10.1177/23094990211047280
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of three different local anesthetic methods for minor hand surgery

Abstract: Purpose: Hemostasis and local anesthetic injection are essential for minor hand surgeries under local anesthesia (LA). Wide awake local anesthesia no tourniquet (WALANT) became popular for achieving hemostasis without a tourniquet. However, a recent study reported that injection is more painful than tourniquet use in minor hand surgery. Therefore, this study aimed to compare three LA methods that differ according to injection and hemostasis, namely, the combination of a tourniquet and buffered lidocaine soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Effective relief of postoperative pain allows a faster postoperative recovery period and is associated with lower morbidity and higher patient satisfaction. Patients with lower postoperative pain scores were the ones who reported higher satisfaction levels (8)(9)(10)(11)(25)(26)(27)(28)(29). Improving postoperative pain control is one of the major issues that should be seriously considered in the field of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Effective relief of postoperative pain allows a faster postoperative recovery period and is associated with lower morbidity and higher patient satisfaction. Patients with lower postoperative pain scores were the ones who reported higher satisfaction levels (8)(9)(10)(11)(25)(26)(27)(28)(29). Improving postoperative pain control is one of the major issues that should be seriously considered in the field of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to WALANT specifically, patients were most concerned with hearing or seeing the procedure as it was being performed and the possibility of feeling pain intraoperatively [67]. Furthermore, Lee et al found that anxiety was higher among WALANT patients when compared with patients who were given local anesthesia with a tourniquet, although there was no change in overall satisfaction [68]. When compared with general anesthesia, however, Davison et al reported that the WALANT cohort had significantly less pre-operative anxiety [23].…”
Section: Patient Satisfaction and Perspectivementioning
confidence: 99%
“…Our study was begun from this idea. 1 As your comment, injection solution's temperature and injection speed have impact on pain while giving LA injection. However, we are carefully concern about stability of buffered lidocaine when warming solution.In previous study, buffered lidocaine dropped to 66.1% of initial concentrations after 4 weeks when stored at 25°C.…”
mentioning
confidence: 99%
“…Therefore, we recommend to use “hole-in-one” injection technique which is introduced in our article. 1,3…”
mentioning
confidence: 99%